Heck, Sonogashira, and Hiyama Reactions Catalyzed by Palladium Nanoparticles Stabilized by Tris-Imidazolium Salt - Planellas, Marc (2014)
Palladium nanoparticles, prepared by the hydrogenation of Pd(dba)2 in the presence of a tris-imidazolium iodide as stabilizer, act as an efficient catalyst for Heck and copper-free Sonogashira reactions with a range of aryl iodides and bromides at 0.2 mol-% Pd loading. Moreover, we describe a convenient protocol for the fluoride-free Hiyama coupling of vinylsilanes with aryl iodides that involves the use of sodium hydroxide as promoter in a methanol/water mixture. Under the developed conditions, one-pot, double Heck and Hiyama–Heck reactions are successfully achieved.